Psycho-educational training for schizophrenic patients at Mankweng Hospital in the Limpopo Province - Raphala, Sabina (University of Limpopo, 2002)
The aim of the study was to assess as to whether psycho education can lead to compliance,and to strengthen the families to be long-term caregivers in Mankweng hospital (psychiatric clinic) of the Limpopo Province. It is included two phases(l) baseline and (2) follow-up. The baseline included of 82 (50 males and 32 females) participants with schizo phrenia. Their (patients) ages ranged from 17 years to 62 years with the mean age of 37.5 (SD=l 0.2). So, forty-one (41) patients were the experimental group who interviewed and also received intervention , and the remaining forty-one(41) were only interviewed at the baseline. After nine moths , follow-up was done, and it included fifty-seven (36 males and 21 females) participants who were followed up at their homes. Thirty-one (31) were the experimental group and twenty-six (26) were the control group. Their ages ranged from 20 years to 62 years with the mean age 39.3 (SD= l2.6). At follow-up , the questionnaire was going along with the Brief Psychiatric Rating Scale for both groups. The results showed that most of the patients were compliant to their medications however ,with no significant differences because of the small sample that represented the population . For instance , not all patients were available at the follow-up session and there were other factors that could harm the effectiveness of research. The research concludes that psycho-education in South Africa can promise to improve health for the individuals only if the psychiatrists continue to educate patients to be effective on their treatment; and it can provide a concrete approach to the development of social and coping skills of the patients and their families.
Thesis (MA. (Psychology)) -- University of the North, 2002.
Keywords: Psycho-educational training; Schizophrenic patients; Transfer of training; Schizophrenics -- Family relationships; Schizophrenics -- Home care -- Limpopo